Dysbindin-1 modulates prefrontal cortical activity and schizophrenia-like behaviors via dopamine/D2 pathways - Papaleo, F; Yang, F; Garcia, S; Chen, J; Lu, B; Crawley, J N; Weinberger, D R (Molecular psychiatry, 2012)
Dysbindin-1 regulates D2-receptor trafficking and is implicated in schizophrenia and related cognitive abnormalities, but whether this molecular effect mediates the clinical manifestations of the disorder is unknown. We explored in dysbindin-1-deficient mice (dys−/−) (1) schizophrenia-related behaviors, (2) molecular and electrophysiological changes in medial prefrontal cortex (mPFC) and (3) the dependence of these on D2-receptor stimulation. Dysbindin-1 disruption altered dopamine-related behaviors and impaired working memory under challenging/stressful conditions. Dys−/− pyramidal neurons in mPFC layers II/III were hyperexcitable at baseline but hypoexcitable following D2 stimulation. Dys−/− were also respectively more and less sensitive to D2 agonist- and antagonist-induced behavioral effects. Dys−/− had reduced expression of Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) and CaMKKβ in mPFC. Chronic D2 agonist treatment reproduced these changes in protein expression, and some of the dys−/− behavioral effects. These results elucidate dysbindin's modulation of D2-related behavior, cortical activity and mPFC CaMK components, implicating cellular and molecular mechanisms of the association of dysbindin with psychosis.